2012
DOI: 10.1242/dev.077073
|View full text |Cite
|
Sign up to set email alerts
|

The floral homeotic protein APETALA2 recognizes and acts through an AT-rich sequence element

Abstract: SUMMARYCell fate specification in development requires transcription factors for proper regulation of gene expression. In Arabidopsis, transcription factors encoded by four classes of homeotic genes, A, B, C and E, act in a combinatorial manner to control proper floral organ identity. The A-class gene APETALA2 (AP2) promotes sepal and petal identities in whorls 1 and 2 and restricts the expression of the C-class gene AGAMOUS (AG) from whorls 1 and 2. However, it is unknown how AP2 performs these functions. Unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 60 publications
(96 reference statements)
0
67
3
Order By: Relevance
“…As shown in Figure 6B, TOE1 enrichment levels at region C (located in the upstream region of FT) and region R (located in the downstream region of FT) were markedly higher than those at other regions. It was recently shown that TOE1 also associates with the FT promoter at region F and region H ( Figure 6A), which contain AT-rich elements (Dinh et al, 2012;Zhang et al, 2015). In our ChIP-qPCR experiments, however, TOE1 enrichment levels at region F and region H were much lower than those at region C and region R ( Figure 6B).…”
Section: Toe1 Binds the Promoter And Downstream Regulatory Region Of contrasting
confidence: 55%
“…As shown in Figure 6B, TOE1 enrichment levels at region C (located in the upstream region of FT) and region R (located in the downstream region of FT) were markedly higher than those at other regions. It was recently shown that TOE1 also associates with the FT promoter at region F and region H ( Figure 6A), which contain AT-rich elements (Dinh et al, 2012;Zhang et al, 2015). In our ChIP-qPCR experiments, however, TOE1 enrichment levels at region F and region H were much lower than those at region C and region R ( Figure 6B).…”
Section: Toe1 Binds the Promoter And Downstream Regulatory Region Of contrasting
confidence: 55%
“…AP2 was recently shown to directly bind the second intron of AG (Yant et al, 2010;Dinh et al, 2012). Using chromatin immunoprecipitation (ChIP), we showed that this region of the second AG intron (supplementary material Fig.…”
Section: Apetala2 Physically Interacts With a Co-repressor And Histonmentioning
confidence: 89%
“…TOE proteins are members of the AP2 family; in addition, AP2 also affects flowering time, possibly through regulating SOC1 and FT expression (Yant et al 2010), and the AP2 protein could bind to AT-rich elements (Dinh et al 2012). Overexpression of TOE1m leads to defects of flower organs (Supplemental Fig.…”
Section: Toes Prevent Precocious Flowering By Repressing Ft Expressionmentioning
confidence: 99%